De novo transcriptome sequencing and analysis of the cuttlefish (Sepiella japonica) with different embryonic developmental stages. Issue 5 (1st October 2021) - Wang, Liyun; Li, Shaogang; Xu, Lele; Li, Yongqin; Chen, Huaxu; Chen, Daohai
Abstract: In this study, embryos of Sepiella japonica from eye primordium formation to the larval growing stage were collected and used for RNA-Seq analysis. A total of 183, 542, 186 clean reads were assembled de novo into 58, 054 unigenes consisting of 54, 118, 228 bp, with the average length at 932 bp and the N50 at 1667 bp. 21, 469 (36.98%) unigenes were annotated at least in one of four databases including non-redundant protein (NR), Swiss-Prot, clusters of orthologous groups of proteins (KOG) and Kyoto Encyclopedia of Genes and Genomes (KEGG). 4460 (7.68%) unigenes were annotated in all databases. Analysis of differentially expressed genes (DEGs) was carried out on embryos at Eye primordium formation stage (SJ1), organ differentiation stage (SJ2), and hatching stage (SJ3). Overall, the current study provided the de novo assembly of S. japonica transcriptome and identified the DEGs and pathways during embryonic development, which will provide a fundamental genetic resource for further functional research.